2010
DOI: 10.1038/npp.2010.179
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hippocampal Cannabinoid CB1 Receptor Actions by Adenosine A1 Receptors and Chronic Caffeine Administration: Implications for the Effects of Δ9-Tetrahydrocannabinol on Spatial Memory

Abstract: The cannabinoid CB 1 receptor-mediated modulation of g-aminobutyric acid (GABA) release from inhibitory interneurons is important for the integrity of hippocampal-dependent spatial memory. Although adenosine A 1 receptors have a central role in fine-tuning excitatory transmission in the hippocampus, A 1 receptors localized in GABAergic cells do not directly influence GABA release. CB 1 and A 1 receptors are the main targets for the effects of two of the most heavily consumed psychoactive substances worldwide: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 76 publications
(99 reference statements)
6
54
0
6
Order By: Relevance
“…Recent work has suggested direct interactions of adenosine A1 and CB1 receptors in the hippocampus (Hoffman et al, 2010;Sousa et al, 2011). To exclude a possible interplay between these two systems of neuromodulators in regulating SWRs, we also compared the adenosine-mediated suppression of SWRs in the absence and presence of AM251.…”
Section: Presynaptic Suppression Of Glutamate Release By Adenosine MImentioning
confidence: 99%
“…Recent work has suggested direct interactions of adenosine A1 and CB1 receptors in the hippocampus (Hoffman et al, 2010;Sousa et al, 2011). To exclude a possible interplay between these two systems of neuromodulators in regulating SWRs, we also compared the adenosine-mediated suppression of SWRs in the absence and presence of AM251.…”
Section: Presynaptic Suppression Of Glutamate Release By Adenosine MImentioning
confidence: 99%
“…Caffeine, a non--selective adenosine receptor antagonist (Pelligrino et al, 2010), elicits: 1) neurostimulant effects, primarily via A1 receptors and the dopamine system (Ferre, 2008;Pelligrino et al, 2010); 2) cerebrovascular effects, primarily via A2A and A2B receptors located on blood vessels (Pelligrino et al, 2010); and 3) arousal enhancing effects, via A2A receptors and the histaminergic arousal system (Ferre, 2008); with tolerance thought to arise as the brain regulates its population of adenosine receptors to reach a new state of equilibrium in response to levels of caffeine chronically present in the body (Jacobson et al, 1996;Ralevic and Burnstock, 1998;Sousa et al, 2011). Studies have shown that administration of 200 --250 mg of caffeine results in reduced CBF (Addicott et al, 2009;Field et al, 2003;Laurienti et al, 2003;Liau et al, 2008;Mulderink et al, 2002;Perthen et al, 2008), possibly accompanied by a reduction in the baseline BOLD signal (during simple motor and visual tasks) (Chen and Parrish, 2009b;Perthen et al, 2008) and changes in the magnitude (Griffeth et al, 2011;Laurienti et al, 2002) and temporal dynamics of the BOLD response Liu et al, 2004;Rack--Gomer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This may have been an important factor since studies have shown that pain receptors, such as adenosine A1 and cannabinoid CB1, can be altered by chronic caffeine use. 24 However, such findings have been primarily in preclinical samples and it is not known how long-term dietary caffeine intake in humans might influence this antinociceptive action.…”
Section: Discussionmentioning
confidence: 99%